Transgenic Mice With Enhanced Neuronal Major Histocompatibility Complex Class I Expression Recover Locomotor Function Better After Spinal Cord Injury - Joseph, M. Selvan (2011)
Mice that are deficient in classical major histocompatibility complex class I (MHCI) have abnormalities in synaptic plasticity and neurodevelopment and have more extensive loss of synapses and reduced axon regeneration after sciatic nerve transection, suggesting that MHCI participates in maintaining synapses and axon regeneration. Little is known about the biological consequences of up-regulating MHCI’s expression on neurons. To understand MHCI’s neurobiological activity better, and in particular its role in neurorepair after injury, we have studied neurorepair in a transgenic mouse model in which classical MHCI expression is up-regulated only on neurons. Using a well-established spinal cord injury (SCI) model, we observed that transgenic mice with elevated neuronal MHCI expression had significantly better recovery of locomotor abilities after SCI than wild-type mice. Although previous studies have implicated inflammation as both deleterious and beneficial for recovery after SCI, our results point directly to enhanced neuronal MHCI expression as a beneficial factor for promoting recovery of locomotor function after SCI.